Early release of circulating tumor cells after transarterial chemoembolization hinders therapeutic response in patients with hepatocellular carcinoma - María L. Espejo-Cruz; Sandra González-Rubio; Juan J. Espejo; Javier M. Zamora-Olaya; María Prieto-Torre; Clara I. Linares; Álvaro Ruiz-Ramas; Álvaro Jiménez-Arranz; Marta Guerrero-Misas; Pilar Barrera-Baena; Antonio Poyato-González; José L. Montero; et al. (Journal of Translational Medicine)
Abstract Background Transarterial chemoembolization (TACE) is the first-line therapeutic option for patients with intermediate-stage hepatocellular carcinoma (HCC). Tumor neovascularization allows tumor growth and may facilitate the release of circulating tumor cells (CTCs) to the bloodstream after TACE. We investigated the relationship between early release of CTCs and radiological response after TACE. Methods Prospective, single-center study including patients with HCC undergoing a first TACE from January 2019 to June 2023. The IsoFlux® system was used to evaluate EpCAM+ CTC counts before TACE, at day 1 (D1), and at day 30 after TACE. Radiological response to TACE was assessed according to the mRECIST criteria one month after the procedure. Tumor vascularity was assessed by an interventional radiologist. Results In all, 48 patients with HCC undergoing TACE were included (age 64.2 ± 7.6 years, 14.6% women). CTC levels increased at D1 (114.0% [IQR 76.5%-178.0%], p = 0.019) and normalized to baseline levels in the first month after TACE (76.5% [IQR 41.3%-131.8%], p = 0.263). Higher CTC counts at baseline (p = 0.009) and at D1 (p = 0.026) were associated with tumor hypervascularity. Larger tumor size [OR: 1.9 (95% CI: 1.1–3.3), p = 0.020] and CTC increase at D1 [OR: 5.3 (95% CI: 1.3–21.0), p = 0.017] were independent predictors of non-response to TACE, especially for those patients with hypervascular lesions. Conclusions A meaningful release of CTCs 24 h after TACE was associated with suboptimal tumor response one month after the procedure. Future studies should evaluate the role of CTC dynamics to select candidates for adjuvant therapy after TACE and to analyze their impact on long-term outcomes.